Undifferentiated pleomorphic sarcoma in the anterior mediastinum: a case report and literature review - Wang, Luyao; Xie, Anyu; Ke, Luqin; Jia, Pingfan; Li, Yuru; Guo, Xing (Frontiers in Oncology, 2024)
Primary undifferentiated high-grade pleomorphic sarcoma (UPS) in the mediastinum is exceptionally rare. This paper reports a unique case of anterior mediastinal UPS in an 84-year-old Asian male presenting with recurrent upper respiratory tract infections and upper abdominal discomfort. Imaging via CT and MRI suggested an invasive thymoma, but postoperative pathology confirmed UPS. Despite radical surgery, local recurrence occurred within three months, and palliative radiotherapy was ineffective. This case provides the first comprehensive imaging data of UPS in the anterior mediastinum, aiming to improve diagnostic accuracy for clinicians and radiologists by summarizing imaging features across various modalities.